(untitled) (Perner’s Contacts, 2010)
The paper deals with traffic organization in the close neighborhood Prerov railway station The possible variants of improve traffic situation in this area and in the individual crossroads are propound by analyze of the present state current In conclusion the variants are assessed and compare with.